Big sisters are bad witches - Hamilton, Morse (New York : Greenwillos Books, 1981)
The sibling rivalry of two sisters improves when a third child on the way promises to turn little sister into big sister
Keywords: Sibling rivalry-Fiction; Brothers and sisters - Fiction; Babies-Fiction